(untitled) (Indian Journal of Public Health Research & Development, 2020)
Introduction: The stress response to surgery, critical illness, trauma, and burns encompasses derangements of metabolic and physiological processes which induce perturbations in the inflammatory, acute phase, hormonal, and genomic responses. The surgery-induced stress response is largely similar to that triggered by traumatic injuries, the duration of the stress response, however, varies according to the severity of injury. Objectives: The objectives of the study were to determine the effectiveness of myotherapy on stress and associate the selected background variables with stress. Method: The research design adopted for the study was randomized controlled trial. The study was conducted among 250 samples,125 in the study and 125 in control group to evaluate the effectiveness of myotherapy on stress among patients subjected to major orthopedic surgeries. The mean age of the study participants were male and female equally distributed. Data were collected and analyzed using descriptive and inferential statistics. Findings: Independent t ‘t’ test revealed that mean difference score was observed in stress at p=0.001 level. Post stress in the study group was significantly associated within previous history of hospitalization at the level of p<001. Conclusion: The study result reveals that the orthopaedic surgical patients suffering with severe stress, economically burdened and functional disability for long time. Myotherapy is one of the complementary medicine which has a great impact on the human body and this study suggested that the practice of myotherapy can decrease the stress.